Optimizing Science Learning through a Problem-Based Approach - Andri Akbar; Rina Asmawati; Herman Juanda (ESENSI: Jurnal Riset Pendidikan, 2025)
Optimizing science learning requires instructional approaches that promote not only conceptual understanding but also higher-order cognitive skills and active learner engagement. This study examines the effectiveness of a structured Problem-Based Learning (PBL) approach in enhancing science learning outcomes, including conceptual understanding, problem-solving skills, critical thinking ability, and student engagement. A quasi-experimental design with a pretest–posttest non-equivalent control group was employed. Participants consisted of students enrolled in a science course, divided into an experimental group receiving PBL-based instruction and a control group receiving conventional teacher-centered instruction. Data were collected using validated instruments measuring conceptual understanding, problem-solving skills, and critical thinking, complemented by student engagement questionnaires and classroom observations. The results indicate that students in the PBL group achieved significantly higher posttest scores across all measured cognitive domains compared to the control group. Notable improvements were observed in students’ ability to apply scientific concepts, analyze complex problems, evaluate evidence, and construct reasoned solutions. In addition, students exposed to PBL demonstrated higher levels of behavioral, cognitive, and emotional engagement during the learning process. Classroom observations revealed that collaborative inquiry, reflection, and active discussion were more prominent in the PBL environment than in conventional instruction. These findings suggest that Problem-Based Learning is an effective pedagogical approach for optimizing science learning outcomes. By engaging students in authentic problem-solving contexts and promoting active knowledge construction, PBL supports deeper understanding and the development of essential scientific skills. The study provides empirical support for the integration of structured PBL models into science education to enhance both learning quality and student engagement.